The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key - Podenas, Sigitas (Zootaxa, 2016)
Two new species of crane flies, Libnotes (Libnotes) charlesyoungi n. sp. and L. (L.) jirisana n. sp. are described. Libnotes (Afrolimonia) plutonis (Alexander, 1924) is described for the first time on the Korean Peninsula. A key for all Korean Libnotes spp. is presented.